Code-Mixing Analysis Used by Edwin in The Web Series Rumah Biru The Series Season 2 - Evelyn Patricia (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study analyzed the code-mixing types and factors used by Edwin in the web series Rumah Biru The Series Season 2. The writer employed a qualitative approach using Muysken’s (2000) and Bhatia and Ritchie’s (2013) theories to analyze Edwin’s sentences that contain code-mixing. The findings revealed that Edwin utilized two types of code-mixing, namely insertion and congruent lexicalization. The alternation type was absent. Those types were motivated by factors, namely participant roles and relationships, situational, reiteration, message qualification, topic-comment/relative clauses, interjections and language attitudes, dominance, and security. Furthermore, some message-intrinsic factors, specifically quotations, hedging, idioms and deep-rooted cultural wisdom were absent. These findings underscore how Edwin’s code-mixing meets the demands of his workplace, enhancing clarity and efficiency in professional communication.